PENGARUH INOVASI PRODUK DAN HARGA TERHADAP MINAT BELI MIE SEDAAP CUP - HENDRAWAN SUROSO, BAYU (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract:The most significant growth occurred in the food of packaged instant noodles industry. By this situation, PT. Wings Food was participate for instant noodle market by releasing a new product marked as "Mie Sedaap Cup". The purpose of this study is for analizing the effect of product innovation and price towards purchase interest. The population for this study are consumers who have ever consumed Mie Sedaap pack and consumers who have never consumed Mie Sedaap Cup. The number of sample in this study is 110 respondents with the sampling technique non probability sampling. The technique for collecting data through questionnaires and documentation while distributing questionnaires conducted at Kelurahan Ketintang, percisely at Ketintang Timur PTT and Ketintang Wiyata. In this study by the t test result, innovation product variables has an influence with purchase interest while the price variables has not influence with purchase interest. Keywords: innovation product, price, and purchase interest.